2012
DOI: 10.1063/1.4729765
|View full text |Cite
|
Sign up to set email alerts
|

Electron-dependent thermoelectric properties in Si/Si1-xGex heterostructures and Si1-xGex alloys from first-principles

Abstract: Unlike phononic thermal conductivity (which is shown in the literature to be reduced due to alloying and has a nearly constant value over a range of compositional variations), electron-dependent thermoelectric properties are shown here, from first-principles, to vary nonlinearly with composition. Of the Si/Si 1 _xGex systems considered, the maximum thermopower observed, which is 10% higher than that of crystalline Si, is obtained for a Si 0 . 875 (J, Ke, K 1 are the Seebeck coefficient or thermopower, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, n(S max ) increases rapidly with the increase of the composition at higher temperatures. Hossain et al [32] have presented a detailed explanation based on the equations for the transport coefficients. The gradient of the Fermi-Dirac distribution broadens at higher temperatures.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…However, n(S max ) increases rapidly with the increase of the composition at higher temperatures. Hossain et al [32] have presented a detailed explanation based on the equations for the transport coefficients. The gradient of the Fermi-Dirac distribution broadens at higher temperatures.…”
Section: Transport Propertiesmentioning
confidence: 99%
“…Although bulk Si has a low ZT of $0.01 at 300 K owing to its high thermal conductivity, recent experimental studies have demonstrated that Si nanowires (SiNW) (with optimal sizes and doping levels) achieve a ZT value of $0.36, owing to the reduced lattice thermal conductivity. 9 Furthermore, several experimental [11][12][13] and theoretical [14][15][16][17] studies have shown that because of their special heterostructure, Si/Ge NWs have superior electronic properties compared to single element SiNW. Among these, radial heterostructure core/shell NWs show remarkably high carrier mobility due to the band offsets in the core/shell nanowires, 15,16 and lower thermal conductivity than SiNW.…”
Section: Introductionmentioning
confidence: 99%